2019
DOI: 10.1016/j.wneu.2019.06.230
|View full text |Cite
|
Sign up to set email alerts
|

Footprint of Reports From Low- and Low- to Middle-Income Countries in the Neurosurgical Data: A Study From 2015 to 2017

Abstract: In 2015, the Lancet Commission on Global Surgery highlighted the disparities in surgical care worldwide. The aim of the present study was to investigate the research productivity of low-income countries (LICs) and low-to middle-income countries (LMICs) in selected journals representing the worldwide neurosurgical data and their ability to report and communicate globally the existing differences between high-income countries (HICs) and LMICs.-METHODS: We performed a retrospective bibliometric analysis using Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…15 Because of these discrepancies, the development of relevant contextspecific clinical practice guidelines useful for LMICs requires the publication of research and other TBI-related papers from these countries. Previous bibliometric studies have already highlighted the contribution of different countries in the worldwide neurosurgical literature, 12,16,25 but none of them have taken into account the respective incidence of disease for each region. We conducted a bibliometric analysis of TBI-related papers published in the last 10 years and in 2018, and after collecting volumes of the pathology for each geographical region, we estimated the capacity of different and heterogeneous areas of the world to report and publish data on TBI.…”
mentioning
confidence: 99%
“…15 Because of these discrepancies, the development of relevant contextspecific clinical practice guidelines useful for LMICs requires the publication of research and other TBI-related papers from these countries. Previous bibliometric studies have already highlighted the contribution of different countries in the worldwide neurosurgical literature, 12,16,25 but none of them have taken into account the respective incidence of disease for each region. We conducted a bibliometric analysis of TBI-related papers published in the last 10 years and in 2018, and after collecting volumes of the pathology for each geographical region, we estimated the capacity of different and heterogeneous areas of the world to report and publish data on TBI.…”
mentioning
confidence: 99%
“…7 If journal publication is a reliable indicator of the quality and quantity of research, then LMICs are severely underrepresented in an international context. 5 In Strengths and limitations of this study ► First qualitative study to explore the challenges of neurosurgeons conducting and disseminating clinical research in low-income and middle-income countries (LMICs). ► Provides an in-depth exploration of neurosurgeons' understanding of how engagement in research could be improved.…”
Section: Introductionmentioning
confidence: 99%
“…4 5 The limited participation of LMICs in research contrasts sharply with their disproportionately high incidence of neurotrauma. 6 In a recent study of research productivity in LMICs, as evidenced by publication in journals, Servadei et al 5 found that only 4.52% of 6708 published reports had an LMIC affiliation. In a further bibliometric study, Africa and Southeast Asia were found to be responsible for less than 3% of publication productivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations